Peramalan Tinggi Gelombang Transmisi Dengan Permodelan Gelombang Irreguler Pada Pemecah Gelombang Kantong Pasir Tipe Tenggelam Menggunakan Artifical Neural Network (ANN) - Muhammad Rico Saputra; Imam Suprayogi; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
There are some conditions and problems in coastal engineering that can’t be solved by mathematical analysis. ANN method is a soft computing method has been usesd to solve many problems in any cases. Judging from the success of the research is the application of ANN method, it is necessary to prove the performance of the ANN method to predict transmission waves for sandbag breakwater.The Incoming wave, period, slope, width crest, freeboard, shape and arrangement of sandbags are the parameter that can be used as the test variables. The process to get the result is consisted by training, testing, and validation process. The algorithm used in the development of ANN model is backpropagation algorithm.The results obtained in this study indicate that the performance of the ANN model that has been made to produce the value of the test statistic parameters of the correlation coefficient (R) and Root Mean Square Error (RMSE) that categorized as a very strong correlation and has small error. The best forecasting scheme obtained that the forecasting which resulted in a correlation coefficient (R) is 0.95111 and RMSE value 0.6529 cm.Keywords: forecasting, ANN, Transmission waves, Breakwater